Nonfunctional overreaching and hepatic adaptations of APPL1 and APPL2 - Gustavo P. Morais (Motriz: Revista de Educacao Fisica, 2017)
Abstract AIMS Previously, we verified that overtrained mice upregulated the TRB3 levels, its association with Akt, and the hepatic concentrations of glycogen. It is known that APPL1 can limit the interaction between TRB3 and Akt, playing an important role in the glucose homeostasis. Thus, we verified the effects of three overtraining protocols on the hepatic levels of APPL1 and APPL2. METHODS Rodents were divided into control (CT), overtrained by downhill running (OTR/down), overtrained by uphill running (OTR/up) and overtrained by running without inclination (OTR). The hepatic contents of APPL1 and APPl2 were measured by the immunoblotting technique. RESULTS Significant elevation of APPL1 observed in the OTR/down and OTR/up groups, as well as the tendency of increase (p=0.071) observed in the OTR group. CONCLUSION These results indicate that this particular protein is likely to participate in the glucose homeostasis previously observed in response to these OT protocols.